Oregano extract fed to pre-weaned dairy calves. Part 2: Effect on ruminal and intestinal morphology of pre-weaned calves - L.A. Ritt; E.C. Modesto; J.A. Guimarães; G. Heisler; A.T.D. Oliveira; V. Fischer (Livestock Science, 2023)

Activated carbon production from industrial yeast residue to boost up circular bioeconomy - Helen R. Modesto; Sherlan G. Lemos; Mikaela S. dos Santos; Jenny S. Komatsu; Maraísa Gonçalves; Wagner A. Carvalho; Elma N. V. M. Carrilho; Geórgia Labuto (Environmental Science and Pollution Research, 2021)

Palatability of the Asian clam Corbicula fluminea (Müller 1774) in an invaded system - P. S. Castro; M. I. Ilarri; V. Modesto; C. Antunes; R. Sousa (Hydrobiologia, 2018)

Acanthocephalan Parasites (Acanthogyrus sp.) of Nile Tilapia (Oreochromis niloticus) as Biosink of Lead (Pb) Contamination in a Philippine Freshwater Lake - Vachel Gay V. Paller; Dan Jacob B. Resurreccion; Christian Paul P. de la Cruz; Modesto Z. Bandal (Bulletin of Environmental Contamination and Toxicology, 2016)

17α,20β,21‐Trihydroxy‐4‐pregnen‐3‐one: the probable maturation‐inducing steroid of the Lusitanian toadfish - T. Modesto; A. V. M. Canário (Journal of Fish Biology, 2002)
17,20β,21‐Trihydroxy‐4‐pregnen‐3‐one (17,20β,21‐P) was identified as the major metabolite of incubations of Lusitanian toadfish Halobatrachus didactylus ovarian follicles with [ 3 H]‐17hydroxyprogesterone. The potency of several steroids in inducing germinal vesicle breakdown of follicle‐enclosed oocytes of Lusitanian toadfish was systematically examined by using an in vitro germinal vesicle breakdown (GVBD) bioassay. 17,20β‐Dihydroxy‐4‐pregnen‐3‐one (17,20β‐P) and 17,20β,21‐P, two confirmed maturation‐inducing steroids (MIS) in teleosts, were the most potent in inducing GVBD with ED 50 s ranging between 9 and 271 nM. Structure‐activity relationships followed similar patterns to what has been observed in similar bioassays, i.e. a vital requirement for 17‐ and 20β‐hydroxyl groups in C21 steroids and a reduction in activity of 14 and 5–6%, respectively, for 5‐pregnene and 5β‐pregnanes compared to 4‐pregnenes. Corticosteroids, testosterone and 17β‐oestradiol were ineffective. Folliculated oocytes stimulated by pituitary homogenate produced 17,20β,21‐P from endogenous substrates in amounts one order of magnitude higher than 17,20β‐P. These results strongly support the hypothesis that 17,20β,21‐P is the likely MIS in this species.

Genetic relationships between Dioscorea alata L. cultivars - V. Lebot; B. Trilles; J.L. Noyer; J. Modesto (Genetic Resources and Crop Evolution, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)